Pelatihan Prosedur Penginputan Nilai Siswa Pada Aplikasi E-Rapor SMA Negeri 1 Lobbo Talaud - Eliyah Acantha M Sampetoding; Iden Balango; Relly Potoboda; Yusri Ambabunga (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
The procedure for inputting student grades in the e-report application at SMA Negeri 1 Lobbo is generally very important considering the purpose of inputting grades is a method that must be done carefully and competently among teachers, both subject teachers, and homeroom teachers. So that there are no errors or mistakes in inputting data and values ​​in the E-Report application. In Student Service, several literature reviews are explained, namely procedures, input, data, grades, schools, students, applications, E-Reports, and SMA. The purpose of this service is to find out how the Procedure for Inputting Student Values ​​in the E-Report Application at SMA N 1 Lobbo and what problems are often faced. So that the author can consider and can provide input, encouragement, for the procedure for Inputting Student Values ​​in the E-Report Application at SMA Negeri 1 Lobbo. In writing this Field Work Practice report, the authors conducted observations, interviews, to obtain result data consisting of profiles, history, vision and mission of SMA Negeri 1 Lobbo, organizational structure, tasks and functions as well as several ways to input student scores on the E-mail application. Reports from before.